(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Growth of the nation in the internationalarena largely depends on its economic growth. One of the crucial factors which influences the economic growth is theability of the people in terms of employment and as well as empowerment.Poverty in the nation has a huge negative concern in terms of nationalprosperity towards future. Further,rural poverty which is strongly rooted in India has always been a negativeconcern. Assistance by rural financialinstitutions has created huge helping hand for rural poor not only to overcomepoverty but also empowering themselves after taking assistance in the form ofloans. The present paper is a fieldbased research study which analyzes the importance of institutional finance forrural poor and also it examines the role of institutional finance for ruralpoor.